2014
DOI: 10.1016/j.diii.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Interest of contrast-enhanced sonography to identify focal nodular hyperplasia with sinusoidal dilatation

Abstract: CEUS seems to be an essential step for the diagnosis of non-typical FNH, such as FNH-sd. This small series highlights the interest of performing both CEUS and MRI for the diagnosis of atypical focal liver lesions, such as FNH-sd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In this study, 23 of 31 focal nodular hyperplasia lesions (74.2%) showed typical vascular patterns, including central stellate vascularity and centrifugal enhancement. These typical vascular patterns on CEUS have been well documented in previous studies, with a wide range of detection rates from 30% to 100% . Among these studies, Luo et al reported sensitivity of 82% for “diffuse enhancement with spoked‐wheel arteries” with Sonazoid, using intermittent scanning with a high mechanical index.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In this study, 23 of 31 focal nodular hyperplasia lesions (74.2%) showed typical vascular patterns, including central stellate vascularity and centrifugal enhancement. These typical vascular patterns on CEUS have been well documented in previous studies, with a wide range of detection rates from 30% to 100% . Among these studies, Luo et al reported sensitivity of 82% for “diffuse enhancement with spoked‐wheel arteries” with Sonazoid, using intermittent scanning with a high mechanical index.…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies have reported that CEUS can provide valuable information about the central feeding artery, spoked‐wheel vascularity, and the centrifugal filling pattern of focal nodular hyperplasia, which can lead to a confident diagnosis. However, most studies have been conducted with a contrast agent other than Sonazoid.…”
mentioning
confidence: 99%